2017
DOI: 10.1007/s13280-017-0936-4
|View full text |Cite
|
Sign up to set email alerts
|

Delivering on seafood traceability under the new U.S. import monitoring program

Abstract: The United States is the world's largest fish importer. Recent reports, however, indicate that 25-30% of wild-caught seafood imported into the US is illegally caught, heightening concerns over the country's significant role in driving Illegal, Unreported, and Unregulated (IUU) fishing. In January 2017, NOAA enacted the Seafood Import Monitoring Program in an effort to combat IUU fishing through mandating improved seafood traceability requirements. This program requires reporting of fisheries data from harvest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 28 publications
0
17
1
2
Order By: Relevance
“…Compared to catch, it is more difficult to identify the countries driving threatened species imports because of the overall lower taxonomic resolution of global seafood trade records. For example, USA has very little industrial reported catch that is not recorded at species level, but almost half of its imported commodities are aggregated records because, like many wealthy nations, it imports seafood from countries with less stringent regulations or management capacity 37 . We likely underestimate the value of imports for wealthy countries and overestimate those of poorer countries because we use ex-vessel prices to compare the value of seafood imports.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to catch, it is more difficult to identify the countries driving threatened species imports because of the overall lower taxonomic resolution of global seafood trade records. For example, USA has very little industrial reported catch that is not recorded at species level, but almost half of its imported commodities are aggregated records because, like many wealthy nations, it imports seafood from countries with less stringent regulations or management capacity 37 . We likely underestimate the value of imports for wealthy countries and overestimate those of poorer countries because we use ex-vessel prices to compare the value of seafood imports.…”
Section: Discussionmentioning
confidence: 99%
“…Developing countries, principal suppliers of snappers, often suffer from weak governance and insufficient financial and technical resources to achieve end‐to‐end traceability, opening doors for illicit conduct (Cawthorn & Mariani, ). Fostering strategic partnerships between supply‐chain actors, nongovernmental organizations, and foreign governments could assist in building infrastructure, expertise, and monitoring‐ and enforcement‐capacity in developing‐world fisheries, while preventing stricter regulations from becoming trade barriers and jeopardizing livelihoods in such nations (Willette & Cheng, ). Last, we recommend that all policies be complemented by appropriate public awareness campaigns on seafood sustainability, fraud, and potential substitutes, creating bottom‐up pressure for transparent labeling and a marketplace less susceptible to trickery through mislabeling.…”
Section: Discussionmentioning
confidence: 99%
“…Di Indonesia, sepanjang bulan Januari hingga Maret 2017 terdokumentasi 23 insiden dan 893 orang yang mengalami keracunan makanan , dan tahun 2017 di Kabupaten Gunung Kidul Yogyakarta terdapat kasus keracunan makanan mencapai 79 orang tanpa ada kematian dengan penyebab keracunan berdasarkan attack rate makanan tertinggi dan berdasarkan hasil pemeriksaan laoratorium, keracunan disebabkan oleh bakteri E.Coli dan Salmonela [1]. Sejak tahun 2019 Amerika Serikat melalui badan pengawas makanan (FDA) mensyaratkan semua produk pangan yang diekspor ke Amerika Serikat harus melampirkan dokumen Seafood Import Monitoring Program (SIMP) yang berisikan data asal usul ikan, wilayah penangkapan, lokasi pendaratan, nama kapal nelayan, nama pemasok, data perusahaan pengolahan produk perikanan [2]. SIMP merupakan program untuk impor produk makanan laut tertentu, persyaratan pelaporan dan pencatatan yang diperlukan untuk mencegah penangkapan ikan ilegal, tidak dilaporkan dan tidak diatur (IUU, illegal, unreported uncontrolled) atau salah saji dari memasuki perdagangan Amerika Serikat untuk menjamin keamanan pangan global dan keberlanjutan sumber daya laut.…”
Section: Pendahuluanunclassified
“…Melalui program seafood import monitoring program, diterapkan dalam upaya memerangi IUU fishing melalui mandat peningkatan persyaratan keterlacakan makanan laut, yang mensyaratkan pelaporan data perikanan dari panen hingga kedatangan di perbatasan Amerika Serikat. Penelitian ini memberikan komentar mendalam tentang potensi kebijakan Amerika Serikat untuk memimpin dengan memberi contoh dan meningkatkan sumber daya alam esensial yang lebih dari satu miliar orang di seluruh dunia bergantung pada nutrisi dan mata pencaharian, dan program ini berhasil apabila menerapkan teknologi terbaik yang tersedia dan paling tepat dan membangun kapasitas pemantauan dan penegakan hukum di antara negara-negara perdagangan [2]. Keterlacakan umumnya sebagai persyaratan teknis bagi bisnis untuk memenuhi peraturan pemerintah tentang keamanan pangan, penarikan kembali makanan, dan pelabelan produk dari negara asal [3].…”
Section: Pendahuluanunclassified